2006
DOI: 10.1002/uog.2721
|View full text |Cite
|
Sign up to set email alerts
|

Placental volume measured by three‐dimensional ultrasound in the prediction of fetal α0‐thalassemia: a preliminary report

Abstract: Objective To evaluate the use of placental volume measured by three-dimensional (3D)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
(41 reference statements)
1
25
0
1
Order By: Relevance
“…The 30° rotation method resulted in a wider range of intra-observer 95% limits of agreement than the 15° method. Differing reproducibility data have been reported for 3D measurements and analyses of placental volume, varying from relatively poor to highly similar intra-and inter-observer agreement [39,42-46]]. The results of this study are similar to those of Cheong et al, who reported that measurements made with VOCAL 30°, in an ex-vivo experiment, were faster to complete, but associated with significantly higher variability than those made with VOCAL 12° [18].…”
Section: Discussionsupporting
confidence: 75%
“…The 30° rotation method resulted in a wider range of intra-observer 95% limits of agreement than the 15° method. Differing reproducibility data have been reported for 3D measurements and analyses of placental volume, varying from relatively poor to highly similar intra-and inter-observer agreement [39,42-46]]. The results of this study are similar to those of Cheong et al, who reported that measurements made with VOCAL 30°, in an ex-vivo experiment, were faster to complete, but associated with significantly higher variability than those made with VOCAL 12° [18].…”
Section: Discussionsupporting
confidence: 75%
“…Aside from the 2‐dimensional placental thickness measurement described above, it has been reported that 3‐dimensional sonography might also facilitate the analysis of placental volume in early pregnancy 46 . Although its efficiency in predicting fetuses with α‐thalassemia was not validated in a pilot study 47 because of the limited number of affected fetuses (11 cases), we still believe that further 3‐dimensional sonographic studies with larger sample sizes could be helpful.…”
Section: Sonographic Markers Of Fetal α‐Thalassemia Majormentioning
confidence: 99%
“…Placental volume measurement and uterine artery Doppler in the first trimester may be used to identify women at risk of subsequent development of pregnancy complications such as pre‐eclampsia, pregnancy‐induced hypertension, preterm placental abruption or fetal growth restriction2–4. Furthermore, assessment of placental volume may be useful in first‐trimester risk assessment for chromosomal anomalies5 and homozygous α 0 ‐thalassemia6.…”
Section: Introductionmentioning
confidence: 99%